Interval Cancers in Colorectal Cancer Screening - MATSUDA, Kazuo; WATANABE, Kunishige (Journal of Gastroenterological Mass Survey, 2005)
Although there is sufficient evidence to suggest that colorectal cancer screening is effective in reducing the mortality from colorectal cancer, interval cancers discovered in fecal occult bloodnegative individuals through examinations other than the screening are a problem. In order to clarify the situation of interval cancer, examinees of checkups conducted in 1992-1995 (144, 295 subjects; ratio of subjects who required thorough examination: 5.1%; ratio of subjects who underwent thorough examination: 74.0%) underwent cancer registration and were followed up for 2 years. Of the 203 patients in which invasive cancer was discovered, 98 cases were true positive and 25 were false negative on thorough examination; 19 did not undergo thorough examination; 33 were false negative for occult blood and were found at annual or biennial screenings; 28 patients had interval cancer, accounting for 14%. The interval cancer was located in the right colon in 14 of the 28 patients, and this was more frequent than in the other 4 groups (P=0.089). The degree of differentiation of the cancer was poor in 4 of the 28 patients, but this frequency is significantly higher than that in the other groups (P<0.001). The cumulative 5-year survival rate was 63.9% in cases of interval cancer, significantly lower than those in the other groups: 96.7% in the cases which were false negative for occult blood and which were found in annual or biennial screenings and 82.0% in the true positive group. But it is noteworthy that the cumulative survival rate for interval cancer is equal to that of the cancers discovered in people who were not screened.